Pendapatan Asli Daerah : Suatu analisis efektivitas pengelolaan pajak dan retribusi daerah Kabupaten Malaka - Seran, Marisa S B (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims to find out the effectiveness of local tax management and local levies on local original income (PAD) of Malacca Regency. Using sekuder data from BPKAD Malaka Regency in 2016-2020. The model used is ratio analysis. The results showed that the Tax Management of Malaka Regency And The Management of The Malacca Regency Levy in 2016 to 2020 were in the ratio range above 100% so it fell into the category of Very Effective.